Effects of 15% carbamide peroxide and 40% hydrogen peroxide on the microhardness and color change of composite resins. - Sedighe Sadat Hashemi Kamangar; Kiana Kiakojoori; Mansoore Mirzaii; Mohammad Javad Kharazi Fard (Tehran University of Medical Sciences, 2014)
The aim of this study was to determine the effects of 40% hydrogen peroxide and 15% carbamide peroxide on microhardness and color change of a silorane-based composite resin in comparison with two methacrylate-based composites.Fifty-four disc-shaped specimens (A3 shade) were fabricated of Filtek P90 (P90), Filtek Z350XT Enamel (Z350) and Filtek Z250 (Z250) (3MESPE) (n=18). The samples of each composite were randomly divided into three subgroups of 6. The control subgroups were immersed in distilled water; the test groups were exposed to Opalescence Boost (OB) once; and Opalescence PF (OP) (Ultradent) for two weeks. Vickers microhardness testing and a spectrophotometric analysis of the color of samples were performed before and after each intervention.The baseline microhardness of P90 was significantly lower than that of the other two composites (P=0.001), but no difference was found between Z250 and Z350 in this respect (P=0.293). Bleaching treatments significantly decreased the microhardness of Z250 and Z350 (P< 0.001), but no change was observed in P90 test and control subgroups (P> 0.05). No significant difference was detected between the two types of bleaching (P>0.05). After bleaching with OB, ΔE value was measured to be 3.12(1.97), 3.31(1.84) and 3.7(2.11) for P90, Z250 and Z350, respectively. These values were 5.98(2.42), 4.66(2.85) and 4.90(2.78) after bleaching with OP with no significant difference.Bleaching decreased the microhardness of methacrylate-based but not silorane-based composites. Although no significant differences were found in ΔE of composites, ΔE of all groups did not remain in the clinically acceptable range after bleaching except for P90 after bleaching with 40% H2O2 (ΔE < 3.3).